Temporal Variations of the Mole Fraction, Carbon, and Hydrogen Isotope Ratios of Atmospheric Methane in the Hudson Bay Lowlands, Canada - Fujita,R; Morimoto,S; Umezawa,T; Ishijima,K; Patra,PK; Worthy,DEJ; Goto,D; Aoki,S; Nakazawa,T (Journal of Geophysical Research: Atmospheres, 2018)
©2018. American Geophysical Union. All Rights Reserved. We have conducted simultaneous measurements of the mole fraction and carbon and hydrogen isotope ratios (δ13C and δD) of atmospheric methane (CH4) at Churchill (58°44′N, 93°49′W) in the northern part of the Hudson Bay Lowlands (HBL), Canada, since 2007. Compared with the measurements at an Arctic baseline monitoring station, Ny-Ålesund, Svalbard (78°55′N, 11°56′E), CH4 mole fraction is generally higher and δ13C and δD are lower at Churchill due to regional biogenic CH4 emissions. Clear seasonal cycles in the CH4 mole fraction, δ13C, and δD are observable at Churchill, and their seasonal phases in summer are earlier by approximately 2 weeks than those at Ny-Ålesund. Using the one-box model analysis, the phase difference is ascribed to the different seasonal influence of CH4 emissions from boreal wetlands on the two sites. Short-term CH4 variations are also observed at Churchill throughout the year. The analysis of the observed isotopic signatures of atmospheric CH4 confirmed that the short-term CH4 variations are mainly produced by biogenic CH4 released from the HBL wetlands in summer and by fossil fuel CH4 transported over the Arctic in winter. Forward simulations of an atmospheric chemistry-transport model, with wetland CH4 fluxes prescribed by a process-based model, show unrealistically high CH4 mole fractions at Churchill in summer, suggesting that CH4 emissions assigned to the HBL wetlands are overestimated. Our best estimate of the HBL CH4 emissions is 2.7 ± 0.3 Tg CH4 yr−1 as an average of 2007–2013, consistent with recent estimations by inverse modeling studies.